The Effect of Short- term Physical Activity (treadmill running) on Spatial Learning and Memory in the Intact and Morphine Dependent Male rats - Hamid Azizi Malekabadi; Hojjatollah Alaei; Mahmoud Hosseini (مجله دانشکده پزشکی اصفهان, 2008)
Abstract It has been shown that the activity of some neurotransmitters may be changed by exercise. It can also affect on pleasure center through Opioid Systems and releasing neurotransmitters. Based on the effect of exercise, in this research, we studied the effect of exercise and physical activity with treadmill running on spatial learning and memory in the intact and morphine dependent male rats.